1988
DOI: 10.1111/j.1471-4159.1988.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a New Biogenic Aldehyde Adduct by Incubation of Tryptamine with Rat Brain Tissue

Abstract: Tryptamine was degraded by incubation with rat brain homogenate to an unknown product. The reaction was stimulated by the nonionic detergents Triton X-100 and Lubrol PX and less by the zwitterionic detergent 3-[(3-cholamidopropyl)dimethylammonio]1-propanesulfonate (CHAPS). The same results were obtained with pig brain and bovine brain. The monoamine oxidase inhibitor pargyline inhibited the reaction strongly, indicating the participation of the enzyme on the reaction. Addition of 17,000 g supernatant from rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…This data further confirmed the structure of 5-HITCA, which was reported to form from 5-HIAL and L-Cys in aqueous media and in tissue incubated with 5-HT and L-Cys (13)(14)(15).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This data further confirmed the structure of 5-HITCA, which was reported to form from 5-HIAL and L-Cys in aqueous media and in tissue incubated with 5-HT and L-Cys (13)(14)(15).…”
Section: Discussionsupporting
confidence: 87%
“…Susilo and colleagues (14,15) reported the formation of ITCA from incubations of brain homogenates with tryptamine, later documenting the formation of 5-HITCA from 5-HT in brain homogenates, and Singh and Dryhurst (13) performed a follow-up study on the mechanism of formation. As discussed herein, the current study expands on these prior works, incorporating knowledge based upon the formation pathway in specific central and enteric nervous system structures, the involvement of various enzymes, as well as the potential participation of other thiols.…”
Section: Discussionmentioning
confidence: 99%
“…ITCA was synthesized from indole-3-acetaldehyde bisulfite and L-cysteine as described by Susilo et al (1988). The identity of the substance was confirmed by FAB-MS, nuclear magnetic resonance spectrometry, and carbon-13 magnetic resonance spectrometry as reported by Susilo et al (1987Susilo et al ( , 1988.…”
Section: Synthesis Of Itca and ['4c]itcamentioning
confidence: 99%
“…Recently, we have isolated a new biogenic aldehyde adduct following the incubation of tryptamine with brain homogenate (rat, bovine, or pig brain). The com-pound could be identified by several methods as (4R)-2 4 3'-indolylmethy1)-1,3-thiazolidine-4-carboxylic acid (ITCA), a condensation product of IAAL with the amino acid L-cysteine (Susilo et al, 1987(Susilo et al, , 1988. We have suggested that analogous molecules mmay be formed by the reaction of aldehydes with primary amines and sulfhydryl groups bearing macromollecules present in the brain.…”
mentioning
confidence: 99%
“…There is evidence that the metabolism of tryptamine in pig and rat brain can yield a condensation product formed by a spontaneous interaction between indoleacetic acid and free L-cysteine (Susilo et al, 1987(Susilo et al, , 1988. This product showed selective inhibition of MAO A rather than MAO B.…”
Section: Discussionmentioning
confidence: 99%